2023
DOI: 10.3390/plants12040934
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Methanolic Ajwa Seed Extract on Lipopolysaccharide-Induced Memory Dysfunction and Neuroinflammation: In Vivo, Molecular Docking and Dynamics Studies

Abstract: Islamic literature has indicated that daily consumption of Ajwa dates heals a variety of chronic diseases and disorders. The current research investigates the neuroprotective effect of methanolic Ajwa seed extract (MASE) on lipopolysaccharide (LPS)-induced cognitive deficits using multiple approaches. For animal studies, MASE (200 and 400 mg/kg, p.o.) was administrated for thirty consecutive days, and four doses of LPS (250 µg/kg, i.p.) were injected to induce neurotoxicity. Memory functions were evaluated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…These results support the protective effect of PDF against LPS-induced behavioural changes in animals. These results are in agreement with the recent study on the neuroprotective activities of Ajwa seed extract in toxin-induced neuronal insults in animals [27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results support the protective effect of PDF against LPS-induced behavioural changes in animals. These results are in agreement with the recent study on the neuroprotective activities of Ajwa seed extract in toxin-induced neuronal insults in animals [27].…”
Section: Discussionsupporting
confidence: 93%
“…It was evident by its attenuation of behavioural changes, restoration of antioxidant levels, reduction of oxidative and nitrative stress, reduction of proinflammatory cytokines, restoration of water and food intake and attenuation of ALT and AST in LPS-treated animals. These findings are in agreement with research data published on Ajwa dates as neuroprotective and beneficial in memory improvement in neuro-compromised animals [ 27 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Generally, the animals dislike staying in open and elevated places and prefer to stay in closed and dark areas. Furthermore, shorter TL values support the improvement of their spatial memory [25]. The results of this present study revealed that the extension of TL values on days 1 and 2 was recorded after four doses of DOX in the EPM test, which indicates impairment of learning and memory in rats.…”
Section: Discussionsupporting
confidence: 69%
“…Firstly, the EPM test was conducted over a period of two days, beginning on day 26 of the treatment timeline, with the subsequent day designated as the retention phase. The EPM test is a widely used neutral behavioral model to study the ability of animals to learn and remember [ 38 , 42 ]. Normally, animals tend to avoid open and elevated areas while exhibiting a preference for closed and dark areas.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, animals tend to avoid open and elevated areas while exhibiting a preference for closed and dark areas. Additionally, shorter TL values indicate improved spatial memory [ 42 ]. The study findings revealed that on the first day of the EPM test, the ACR + IAE co-administration group exhibited significantly longer TL values and a decline in spatial memory in relation to the control group.…”
Section: Discussionmentioning
confidence: 99%